Developmental effects of fractionated low-dose exposure to gamma radiation on behaviour and susceptibility of the cholinergic system in mice. (2nd July 2016) - Buratovic, Sonja; Stenerlöw, Bo; Fredriksson, Anders; Sundell-Bergman, Synnöve; Eriksson, Per
Abstract: Purpose : To investigate whether neonatal exposure to fractionated external gamma radiation and co-exposure to radiation and nicotine can affect/exacerbate developmental neurotoxic effects, including altered behavior/cognitive function and the susceptibility of the cholinergic system in adult male mice.Materials and methods : Neonatal male Naval Medical Research Institute (NMRI) mice were irradiated with one 200 mGy fraction/day and/or exposed to nicotine (66 μ g/kg b.w.) twice daily on postnatal day (PND) 10, 10–11, 10–12 or 10–13 (nicotine only). At 2 months of age the animals were tested for spontaneous behavior in a novel home environment, habituation capacity and nicotine-induced behavior.Results : Fractionated irradiation and co-exposure to radiation and nicotine on three consecutive days disrupted behavior and habituation and altered susceptibility of the cholinergic system. All observed effects were significantly more pronounced in mice co-exposed to both radiation and nicotine.Conclusions : The fractionated irradiation regime affects behavior/cognitive function in a similar manner as has previously been observed for single-dose exposures. Neonatal co-exposure to radiation and nicotine, during a critical period of brain development in general and cholinergic system development in particular, enhance these behavioral defects suggesting that the cholinergic system can be a target system for this type of developmental neurotoxic effects.